Worldviews and diversity: freedom of expression and teaching about the mosque - Revell, Lynn (Journal of Religious Education, 2021)
The ability to encourage pupils to engage with diversity is crucial for Religious Education (RE) teachers who believe that the capacity to negotiate difference with integrity and openness is key to living well in a modern liberal society. This article is not about the need to address diversity in RE, that argument has been made thoroughly from a number of perspectives (Barnes, 2014; Jackson, 2004). The focus of this article is the way we engage with diversity, that is a plurality of often opposing views, ways of living and community living. We argue that the dominant paradigm within RE, the World Religions model, works to minimise difference through the presentation of essentialised constructs of religiosity. We contrast the World Religions approach to a liberal educational model which encompasses difference as part of a deep engagement with knowledge itself. Using examples from lessons available from a widely used teachers’ web site in the UK on the mosque we show how the World Religions approach ignores or downplays the significance of historical, cultural, social and theological differences between beliefs and thus serves to discourage exploration of issues that may be controversial or offensive. After a consideration of the educational benefits of a liberal approach to learning, we show how, using the example of teaching about the mosque, a Worldviews approach, can facilitate a focus on difference and the individual, that upholds the liberal educational promise for a multidisciplinary understanding of religion and belief. Throughout the article we draw on examples of work designed to create resources for teaching Islam through a Worldviews approach funded by Culham St Gabriel.